If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -60 = 7493 Reorder the terms: -60 + y = 7493 Solving -60 + y = 7493 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + y = 7493 + 60 Combine like terms: -60 + 60 = 0 0 + y = 7493 + 60 y = 7493 + 60 Combine like terms: 7493 + 60 = 7553 y = 7553 Simplifying y = 7553
| (6n-10)/(n-4) | | 14-x=2+5 | | 0.4x-2=0.6x | | 0.4y+2x=1.2 | | 18x^2+5x-72=0 | | X+18=296 | | 6x-4y-3x+4=0 | | 5n-28=-64+9n | | 27=90c | | 140=-10n | | 6y+7=4y-3 | | S=12-a/4 | | -6x+20=-4x-22 | | 4/3=r-8/9 | | Y+20=5y-8 | | 0.25+9=-12 | | 9x-6=3(-4+3x)+6 | | (x+4)+(4y-8)=180 | | 0.25+9=-13 | | 12x-24=4x-32 | | 28v-21= | | 9x-5=9(x+2)-11 | | 4y+2=-3y+19 | | g(f(-2))= | | 3.75w=35 | | 5x-3=12x-30 | | (4cotx-1)(sinx+1)=0 | | 27=9t-9 | | 2x+4-4x=-2(X-2) | | 5n+6=10n+3 | | 2(3+5x)-5=4 | | 8-5x=-2y |